2007
DOI: 10.1080/09670870701469872
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between resistance factors and treatment efficacy when bromadiolone was used against anticoagulant-resistant Norway rats (Rattus norvegicusBerk.) in Wales

Abstract: We investigated the relationship between the severity and incidence of resistance among Norway rats (Rattus norvegicus) on a farm in Wales and the subsequent outcome of a practical rodent control operation. Bromadiolone resistance factors were estimated for rats trapped on the farm using the blood clotting response test, and were found to be 2 to 3 for male rats and approximately 6 for females. The incidence of resistance in the rat population was high. Infestation size was estimated by census baiting and trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 8 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…To overcome the latter in human haematology, all thromboplastin reagents are calibrated against a WHO standard reference material (Denson 1998). BCRtests for anticoagulant rodenticides were recently adapted to accommodate such standardisation, not available when earlier BCR-tests were developed; and baselines for most anticoagulants were reassessed (RRAC 2003;Prescott et al 2007). Investigations presented in this paper are the first proof of this new method and derived baselines to compare strains of wild Norway rat, and to investigate the degree of resistance in wild populations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…To overcome the latter in human haematology, all thromboplastin reagents are calibrated against a WHO standard reference material (Denson 1998). BCRtests for anticoagulant rodenticides were recently adapted to accommodate such standardisation, not available when earlier BCR-tests were developed; and baselines for most anticoagulants were reassessed (RRAC 2003;Prescott et al 2007). Investigations presented in this paper are the first proof of this new method and derived baselines to compare strains of wild Norway rat, and to investigate the degree of resistance in wild populations.…”
Section: Discussionmentioning
confidence: 96%
“…Surprisingly, only on one out of five farms in the resistance area of Wales could a considerable incidence and degree of resistance be confirmed. More details about the study on that farm are reported elsewhere (Buckle et al 2007). The low level of resistance on four out of five farms allows us to conclude that the situation has apparently not worsened in Wales, even though anticoagulants have been used there for decades after first resistance was reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations